2003
DOI: 10.1292/jvms.65.825
|View full text |Cite
|
Sign up to set email alerts
|

Aggregability and Post-Transfusion Survival of Canine Platelets in Stored Whole Blood

Abstract: ABSTRACT. The effects of whole blood storage time on platelet aggregation and on post-transfusion platelet survival time were assessed in dogs. Citrate phosphate dextrose adenine-1 (CPDA-1) was used as a blood cell preservative. Storage time dependent decay of platelet aggregability was assessed. Platelet aggregation responses to collagen and ADP were maintained for at least 8 hr at room temperature. During blood storage, immunoglobulin became nonspecifically bound to platelets, suggesting the potential for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, frozen platelets in some preparations have significantly decreased activity 197,198 . Platelets in canine whole blood retain activity for up to 8 hours after collection when stored at room temperature 199 . Thus, whole blood transfusion may be a better solution to treat thrombocytopenia and/or platelet dysfunction in veterinary patients with trauma.…”
Section: Introductionmentioning
confidence: 99%
“…However, frozen platelets in some preparations have significantly decreased activity 197,198 . Platelets in canine whole blood retain activity for up to 8 hours after collection when stored at room temperature 199 . Thus, whole blood transfusion may be a better solution to treat thrombocytopenia and/or platelet dysfunction in veterinary patients with trauma.…”
Section: Introductionmentioning
confidence: 99%
“… There are other preservatives, Adsol and Nutricel, for example, that can extend the storage of packed red blood cells for approximately 5 weeks, but the viability of platelets stored in whole blood for this extended amount of time has not been proven. One prospective study involving 18 dogs used FWB collected in CPDA1 to assess platelet aggregation with storage time and temperature, suggesting that canine platelets maintain viability when stored at room temperature for up to 8 hours in CPDA1 treated FWB . Once FWB is collected it should be stored at room temperature for a maximum of 8 hours and continuously rotated .…”
Section: Platelet Productsmentioning
confidence: 99%
“…One prospective study involving 18 dogs used FWB collected in CPDA1 to assess platelet aggregation with storage time and temperature, suggesting that canine platelets maintain viability when stored at room temperature for up to 8 hours in CPDA1 treated FWB . Once FWB is collected it should be stored at room temperature for a maximum of 8 hours and continuously rotated . However, Hughes et al performed a prospective study in which 10‐CPD whole blood units from human volunteers were collected and divided into 2 equal volumes, one‐half of each unit was then stored at 19°C (66.2°F) and the other half was stored at 25°C (77°F).…”
Section: Platelet Productsmentioning
confidence: 99%
“…The reason for this non-specific binding is not clear. In addition, most of the platelets were lost during the complicated preparation process, and it was concluded that positive platelets prepared by this chemical coupling method were not an appropriate positive control.IgM positive platelets were prepared by storage of EDTA-treated whole blood at 4C overnight as this has been reported to result in nonspecific binding of IgM to canine platelets [6,12]. Platelets strongly positive for IgG, IgM and C3 (IgG/IgM/C3 triple positive) were prepared by adding 5 mg/ml of lipopolysaccharide (LPS; from Escherichia Coli O127:B, Sigma-Aldrich Corporation, St. Louis, MO, U.S.A.) to citrated PRP and incubation at 37C for 30 min.…”
mentioning
confidence: 99%
“…The appropriate discrimination gate for platelets by forward-and side-light scatters was set as previously reported [12]. Background fluorescence was detected using negative control platelets similarly incubated with each of the FITC-conjugated antibodies described above.…”
mentioning
confidence: 99%